The body balance variability of judo athletes during a contest - Serrano-Huete, V.; Latorre-Román, P. A.; García-Pinillos, F.; Romero-Franco, N.; Morcillo-Losa, J. A.; Párraga-Montilla, J. A. (Archives of Budo, 2021)
Background and Study Aim: One important aspect to know with accuracy and with influence in a judo contest is the balance response that it has on athletes. The purpose was to know the variability in body balance during the successive bouts of a judo contest and possible loss percentages in this ability. Material and Methods: Twenty-two men performed five 5-minute bouts with 15 minutes of passive rest. Immediately after each bout, in rest time, balance abilities indicators were tested in a Sway test: centre or pressures (COP), ellipse of area (EA), Sway long (SL) and mean velocity (MV) in dominant (D), non-dominant (ND) and both legs (B). To compare baseline test data and successive bouts, ANOVA was used. Results: ANOVA revealed significant differences in EAD (ellipse of area dominant leg) p = 0.05, SLND (Sway long no dominant leg) p<0.001, SL2 (Sway long both legs) p = 0.009, MVND (mean velocity no dominant leg) p = 0.01 and MVD (mean velocity dominant leg) p = 0.003. In percentages, some decreases of 51.24% in EAD, 44.92% in SLND, 24.48% in SLB, 62.10% in MVND, 27.18% in MVD and 48.86% in MV2 (mean velocity both legs) were found. Fifteen minutes of rest-time was not enough for recovery the baseline levels in body balance abilities. Conclusions: The balance ability is modified during a judo contest. There is an important loss that affects to assessment of dominant, no dominant and mean values to both legs. Due to the fact that there are a high variability of situations that occurs in judo and individuals adaptations postural to aim a high performance, there is not a proportional loss in balance that in others capacities.